'Dopamine agonist Phobia' in Parkinson's disease: when does it matter? Implications for non-motor symptoms and personalized medicine. (1st September 2020) - Rota, Silvia; Boura, Iro; Batzu, Lucia; Titova, Nataliya; Jenner, Peter; Falup-Pecurariu, Cristian; Chaudhuri, K Ray
ABSTRACT: Introduction: Dopamine agonists have been widely used to treat patients with Parkinson's disease, but concerns related to their well-known side effects might prevent their use even when indicated. In this review, the authors describe for the first time the concept of 'Dopamine Agonist Phobia', a pharmacophobia that the authors believe might affect clinicians, and they provide evidence of the benefits of dopamine agonists, focusing on non-motor symptoms. Areas covered: The authors performed an extensive literature research, including studies exploring the use of dopamine agonists for the treatment of non-motor symptoms. The authors indicate the highest level of evidence in each section. Expert opinion: 'Dopamine Agonist Phobia' may preclude valid therapeutic options in selected cases, specifically for the treatment of non-motor symptoms. Thus, the authors propose a personalized approach in Parkinson's disease treatment, and encourage a thoughtful use of dopamine agonists, rather than an overall nihilism.